2021
DOI: 10.3389/fphar.2021.640012
|View full text |Cite|
|
Sign up to set email alerts
|

Dose Dependent Antimicrobial Cellular Cytotoxicity—Implications for ex vivo Diagnostics

Abstract: Introduction:Ex vivo and in vitro diagnostics, such as interferon-γ (IFN-γ) release enzyme linked ImmunoSpot (ELISpot) and flow cytometry, are increasingly employed in the research and diagnostic setting for severe T-cell mediated hypersensitivity. Despite an increasing use of IFN-γ release ELISpot for drug causality assessment and utilization of a range of antimicrobial concentrations ex vivo, data regarding antimicrobial-associated cellular cytotoxicity and implications for assay performance remain scarcely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…A maximal cytotoxicity of 50% was seen at concentrations above 62.5 μg/mL (66.8 μM) for EIPE-1 , whereas 30% cytotoxicity was seen for DBI at 250 μg/mL (617 μM). Cytotoxicity increased in a dose-dependent manner with increasing EIPE-1 concentrations, similar to what has been observed in other antimicrobials . However, DBI exhibited no cytotoxicity in concentrations up to 125 μg/mL (Figure ).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…A maximal cytotoxicity of 50% was seen at concentrations above 62.5 μg/mL (66.8 μM) for EIPE-1 , whereas 30% cytotoxicity was seen for DBI at 250 μg/mL (617 μM). Cytotoxicity increased in a dose-dependent manner with increasing EIPE-1 concentrations, similar to what has been observed in other antimicrobials . However, DBI exhibited no cytotoxicity in concentrations up to 125 μg/mL (Figure ).…”
Section: Resultssupporting
confidence: 83%
“…Cytotoxicity increased in a dose-dependent manner with increasing EIPE-1 concentrations, similar to what has been observed in other antimicrobials. 29 However, DBI exhibited no cytotoxicity in concentrations up to 125 μg/mL (Figure 2). The cytotoxicity seen for EIPE-1 required 4−5fold greater concentrations and prolonged exposure (24 h) than the MIC determined against S. aureus, demonstrating that the amount of EIPE-1 needed to inhibit MRSA growth is well below concentrations that induce host cell cytotoxicity.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…2 Historically, these were performed using the patients' peripheral blood mononuclear cells (PBMCs), but new research has shown increased sensitivity using blister fluid cells (BFCs), 4 varied cut-offs and utilising non-cytotoxic drug concentrations. 5,6 Both assays have acceptable sensitivity with ELISpots demonstrating a sensitivity of 52% in SCAR with a specificity of 100% and LTT reported sensitivity of 27%-74% and specificity of 85%-100%. 3 Further work is required to understand drug metabolites to increase the sensitivity of these assays, as shown with oxypurinol for allopurinol and 4-nitrosulfamethoxazole for TMP-SMX.…”
Section: Time To Reinvent the Wheel For Drug Causality Diagnostic App...mentioning
confidence: 99%